(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
It is very important to meet the educational requirements set out in the state education standard. One of the current challenges is to educate the young generation in the national spirit, and to turn the State Education Standard into a new national curriculum, which will certainly serve to bring up a harmoniously developed generation.